(untitled) (Fiep Bulletin - online, 2016)
The objective of this study was to analyze the perception of effort in relation to the goal of hypertrophy training. 50 male individuals were selected practitioners in hypertrophy training, an average of 25.14 ± 5.9 years and at least six months of practice. The exercises were bench press and leg press 45 °. We used scale exertion and submaximal test of strength. The results show that the bench press was no difference (p <0.05) between the perception and the real trained -16.4% (-23.9%) and to exercise leg press 45 ° difference (p <0.05) between the perception and the real trained -19.3% (-19.3%). So much for the EPE (Stress Perception Scale), and for% 1RM, the subjects were in training supports for muscular endurance (RML), intensity below the goal of hypertrophy. In the analysis of the bench press 26 (52%) subjects understood the scale (EPE) and 24 (48%) did not understand. To exercise leg press 33 (66%) understood the scale and 17 (34%) did not understand. We conclude that the practitioners did not understand the scale according to the 1RM test and that his training was not consistent intensity goal.